2017
DOI: 10.5194/acp-17-6957-2017
|View full text |Cite
|
Sign up to set email alerts
|

Radiative and climate effects of stratospheric sulfur geoengineering using seasonally varying injection areas

Abstract: Abstract. Stratospheric sulfur injections have often been suggested as a cost-effective geoengineering method to prevent or slow down global warming. In geoengineering studies, these injections are commonly targeted to the Equator, where the yearly mean intensity of the solar radiation is the highest and from where the aerosols disperse globally due to the Brewer-Dobson Circulation. However, compensating for greenhouse gas-induced zonal warming by reducing solar radiation would require a relatively larger radi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 50 publications
0
26
0
Order By: Relevance
“…The decreased forcing efficiency simulated in this study would increase the injected amount to 70 Tg(S) yr −1 to be injected for such a forcing. Adapting a strategy of Laakso et al (2017) with injections following the zenith of the sun or injecting at 15 • N and 15 • S, may slightly reduce the injection rate. However, the spread in the forcing simulated by different models is large (Niemeier and Tilmes, 2017), as is the amount of injected sulfur necessary to generate a certain forcing.…”
Section: Discussionmentioning
confidence: 99%
“…The decreased forcing efficiency simulated in this study would increase the injected amount to 70 Tg(S) yr −1 to be injected for such a forcing. Adapting a strategy of Laakso et al (2017) with injections following the zenith of the sun or injecting at 15 • N and 15 • S, may slightly reduce the injection rate. However, the spread in the forcing simulated by different models is large (Niemeier and Tilmes, 2017), as is the amount of injected sulfur necessary to generate a certain forcing.…”
Section: Discussionmentioning
confidence: 99%
“…Improved adjustments of the aerosol mass distribution and AOD may be possible by varying the location and timing of injections aligned with the location of the divergence of the stream functions of the BDC and considerations of large-scale mixing and transport barriers. Since the TOA imbalance and temperature changes are not directly correlated to AOD changes, and therefore to shortwave radiative forcing, considering transport characteristics of the stratosphere for identifying injection regions may be more efficient than following the maximum intensity of solar radiation, as suggested by Laakso et al (2017).…”
Section: Journal Of Geophysical Research: Atmospheresmentioning
confidence: 99%
“…In this method, a part of solar radiation reaching the surface is back‐scattered by injecting aerosols or their gaseous precursors into the stratosphere, thus resulting in surface cooling. Climate modeling studies have shown that the efficiency (cooling per unit aerosol amount) related to aerosol injection can depend on multiple factors, including type of aerosols (Pope et al, ; Weisenstein et al, ), the aerosol size (Heckendorn et al, ; Rasch et al, ), the altitude, the latitude, and the timing of injection (Kravitz et al, ; Laakso et al, ; Tilmes et al, ).…”
Section: Introductionmentioning
confidence: 99%